Perempuan Dalam Dunia Public Relations - Kurnia, Novi; Putra, I Gusti Ngurah (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Literature review shows that women gain more access to job in public relations. Observation in Yogyakarta shows that women are not easily top position in corporation due to understatement of the role of public relations in organizational structure. Discrimination against women is minimal except on family allowance.